2024
DOI: 10.1182/bloodadvances.2023011992
|View full text |Cite
|
Sign up to set email alerts
|

Early predictive factors of failure in autologous CAR T-cell manufacturing and/or efficacy in hematologic malignancies

Clémentine Baguet,
Jérôme Larghero,
Miryam Mebarki

Abstract: Chimeric Antigen Receptor T-cells (CAR T-cells) therapies have shown significant benefits in the treatment of hematological malignancies, such as B-cell acute lymphoblastic leukemia (B-ALL) and B-cell lymphoma. Despite the therapeutic advances offered by these innovative treatments, failures are still observed in 15-40% of B-ALL and > 50% of B-cell lymphoma patients. Several hypotheses have emerged including CD19 negative or positive relapses, low CAR T-cell activation and/or expansion in vivo or T-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…On UVA, MF was associated with features of disease burden, including LDH > ULN and circulating disease in the peripheral blood on the day of harvest. In the absence of detailed quantitative and qualitative analysis of the harvested material, 33 these findings are potentially suggestive of a disease‐associated qualitative T‐cell defect hampering cell expansion during manufacture. Wang et al have previously demonstrated that T‐cells in the MCL tumor microenvironment (TME) demonstrate decreased expression of activation markers with parallel increased expression of markers associated with exhaustion and senescence, 34 a well‐recognized phenomenon in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On UVA, MF was associated with features of disease burden, including LDH > ULN and circulating disease in the peripheral blood on the day of harvest. In the absence of detailed quantitative and qualitative analysis of the harvested material, 33 these findings are potentially suggestive of a disease‐associated qualitative T‐cell defect hampering cell expansion during manufacture. Wang et al have previously demonstrated that T‐cells in the MCL tumor microenvironment (TME) demonstrate decreased expression of activation markers with parallel increased expression of markers associated with exhaustion and senescence, 34 a well‐recognized phenomenon in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors are associated with CAR-T treatment responses, including the patient features, disease status, previous treatment, tumor characteristic, disease burden, cell starting materials, CAR-T product composition, and T-cell fitness [151,152] (Figure 2B). Here, we summarize recent single-cell studies that address the CAR-T-cell behaviors and their correlation to clinical therapeutic response.…”
Section: Car-t-cell Behaviors Correlate With Clinical Therapeutic Res...mentioning
confidence: 99%
“…Solutions to overcome these problems include developing a more rapid manufacturing process, using off-the-shelf allogeneic CAR-Ts, and decentralising the production of autologous CAR-Ts [ 145 , 181 , 182 , 183 , 184 , 185 ]. Thus, at present, there are still many obstacles limiting the application of CAR-T cell therapy in solid tumors.…”
Section: The Cancer Immunotherapy Strategiesmentioning
confidence: 99%